Problem-based learning through lesson study learning community to enhance students' mathematical communication skills - Susanti, Ely; Suparmi, Etty; Syahrial, Syahrial; Effendi, Firman; Sari, Puspita; Ningsih, Sri Tuti (Jurnal Pendidikan Matematika RAFA, 2023)
The aim of this research is to describe students' mathematical communication skills by integrating information technology in a collaborative problem-based learning model designed by teachers and lecturers through a lesson study learning community. The research subjects were 36 students in grade tenth (X.4) at SMA Srijaya Negara Palembang in the 2023/2024 academic year. This research is a mix method with quantitative and qualitative techniques. This research has four stages, namely: plan, do, see, and retrospective analysis. The instruments of this research are test questions, observation sheets, and interview guidelines. Data analysis techniques use quantitative and qualitative. Test result data is scored based on a scoring rubric. Observation data is a percentage based on the appearance of indicators. Test and observation data are categorized into five categories, namely: very good, good, enough, less, and poor. Based on the results of data analysis, it was found that students were able to speak language and convey ideas for solutions well. However, there are students who have difficulty expressing concepts and reading mathematical notation both in writing and orally. This low ability is influenced by several factors such as low student activity during learning and discussions, low interest, lack of self-confidence, and from the cognitive aspect it is influenced by low levels of accuracy and habits in solving problems. So, it can be concluded that students' mathematical communication skills after learning using a problem-based learning model and integrating information technology through lesson study learning communities are categorized as enough.